Good Character, Good Deeds and Good Speech for Developing Multicultural Islamic Education: An Islamic Concept - Muhtar Arifin Sholeh, Muhammad; Waston; Nirwana AN, Andri; Hidayat, Syamsul (Universitas Muhammadiyah Surakarta, 2023)
This research is qualitative research that aims to develop an Islamic quality-of-life model for Islamic multicultural education. Research is conducted by referring to various sources of writing (literary research), and then formulating with deductive and inductive reasoning (thinking). The four criteria for a successful life (luck, win), namely faith, good deeds, correctness, and patience. These four criteria constitute a unified whole, and should not be broken down or reduced. The word 'sholih' means 'whole' (not broken apart) or 'complete', which is also usually translated as 'good'. Goodness due to wholeness and completeness. Wholeness and completeness in the concept of